Differences in photoperiod‐induced diapause plasticity among different populations of the bark beetle Ips typographus and its predator Thanasimus formicarius. (27th September 2016) - Schroeder, Martin; Dalin, Peter
Abstract: Photoperiod is a common cue for diapause induction in insects. In a warmer climate, the photoperiod‐sensitive life stage can be expected to be reached earlier in the season, when day length is still long, thereby increasing the probability of an additional generation. Populations from four latitudes in Sweden of the tree‐killing bark beetle Ips typographus (L.) and its predator Thanasimus formicarius (L.) (Coleoptera, Cleridae) were reared at day lengths from 8 to 23.5 h. Ips typographus adults were classified as being reproductive or in diapause by dissection. Thanasimus formicarius new generation adults were classified as direct developers, whereas last‐instar larvae in pupal chambers were classified as in developmental diapause. The frequency of reproductive diapause among new generation I. typographus adults was negatively correlated with day length and positively correlated with latitude of population origin. The two northernmost populations included a considerable proportion of individuals that entered reproductive diapause even at the longest day lengths. By contrast, diapause entry in the predator T. formicarius was generally independent of photoperiod and geographical origin. In a warmer climate, two generations per year may be more common for I. typographus in Sweden. The predator is less likely to increase voltinism.